Photocatalytic behaviour of (BiYbO\(_3\))\(_0.5\)-(BaTiO\(_3\))\(_0.5\) - SAMAL, Yasaswi Priyadarshini; PATRA, Subhalaxmi; DAS, Tapan; PADHY, Minakshi (Journal of Metals, Materials and Minerals, 2025)
Different organic compounds like dyes and pharmaceutical contaminants pollute a large amount of water which can increase the chemical oxygen demand in water bodies. The photodegradation of dyes has been widely studied using TiO2-based nanomaterials, which are typical photocatalysts. TiO2 is highly effective in reducing pollutants when exposed to UV light and does not cause secondary pollution. However, TiO2 is only functional when exposed to UV light, which is not ideal for real-world use. This drawback of TiO2 pulls the research towards modified photocatalysts for better yield. In this study, the (BiYbO3)0.5 - (BaTiO3)0.5 material was formulated by solid state reaction technique. This material is crystallized to Tetragonal, P4mm. The nano-rod structure can be observed from the FESEM. The photo degradation behavior of the material is observed against the pollutant i.e. Malachite Green. It is found that the photocatalytic degradation of Malachite green is 92.2% in 60 minutes.